Stress Corrosion Cracking of a Forged Mg-Al-Zn Alloy with Different Surface Conditions - Zhongwei Yin; Fengjuan Liu; Dongdong Song; Shihuan He; Jun Lin; Feng Yu (Journal of Chemistry)
Stress corrosion cracking (SCC) of a forged Mg-Al-Zn magnesium alloy with different surface conditions was studied by the four-point bending test and alternate immersion test in NaCl solution. The results showed that the bare Mg-Al-Zn magnesium alloy has low susceptivity to SCC, and no abrupt rupture happened after the immersion test for 5 days under an initial stress load of 0.15–0.75σ0.2. With microarc oxidation (MAO) coating, corrosion resistance was enhanced, but more surface cracks were induced, and microcracks could be detected inside corrosive pits when the load was 0.75σ0.2, which is similar to the bare alloy. The composite coating totally avoided both SCC and corrosion. The low susceptivity of the forged AQ80M alloy to SCC should be attributed to the fine grain size and even distribution of secondary phases around the grain boundary.